Nurturing the one, supporting the many : the Center for Family Life in Sunset Park, Brooklyn - Hess, Peg McCartt (Columbia University Press, 2003)
Extends a study funded 1993-1997 by the Annie E. Casey Foundation, providing detailed information beyond that in previous publications on the Center for Family Life.